(untitled) (AGROINNOVATSIYА, 2024)
From the initial processing of cotton, drying-cleaning, ginning, lintering and processing of fiber waste, there is a large amount of dust. The dust released from the drying-cleaning shop is relatively less, 5-7 mg/m3 in the air of the building where the drying equipment is located. The reason is that the cottons coming to be dried have a high humidity, the moisture in the cotton prevents the separation of small dust from the raw material mass. Large-dispersed dust separates even at high humidity and settles without having time to disperse in the building